Epistemologi Hudā dalam QS 2:185: Analisis Leksikal, Tafsir Klasik, dan Relevansi Kontemporer - Anas Kholik; Muhammad Hariyadi (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
This study aims to examine the meaning of hudā in Qur’an 2:185 as the epistemological foundation through which the Qur’an guides human beings in understanding, evaluating, and verifying truth. Previous research has generally discussed hudā within theological or broad thematic frameworks, resulting in limited exegetical attention to key verses that articulate the epistemic structure of Qur’anic guidance. To address this gap, this study applies a thematic exegesis (tafsīr mawḍū‘ī) approach consisting of three main stages. First, a lexical analysis of the root h-d-y is conducted to map its Qur’anic semantic field, including its core meaning, morphological derivations, and contextual usage across the Qur’an. Second, Qur’an 2:185 is examined through comparative exegesis (tafsīr muqāran), incorporating the interpretations of al-Ṭabarī, Fakhr al-Dīn al-Rāzī, Ibn Kathīr, and M. Quraish Shihab to identify both convergences and divergences in their understanding of hudā. Third, an epistemological synthesis is developed to relate the structural concept of Qur’anic guidance to contemporary challenges, particularly the rise of post-truth discourse, information overload, digital misinformation, and algorithmic bias that increasingly shape modern epistemic environments. The findings indicate that hudā in Qur’an 2:185 encompasses three interconnected epistemic dimensions: (1) dalālah, the directional guidance that orients human cognition toward truth; (2) bayān, the explanatory dimension that clarifies legal, ethical, and theological principles; and (3) tamyīz, the faculty of discerning truth from falsehood through a synergy of revelation, reason, and empirical reality. This study concludes that hudā is not merely spiritual guidance but a coherent Qur’anic epistemology relevant for strengthening scientific ethics, knowledge verification, and intellectual integrity in the digital age.